Investigation of indentation and dry sliding wear behaviour of Al-12.6 wt.% Si-10 wt.% TiB2 composites produced by sequential milling and pressureless sintering - Tekoglu, Emre; Yürektürk, Yakup; Agaogullari, Duygu; Dilawary, Shaikh Asad Ali; Baydogan, Murat; Ovecoglu, M. Lutfi (Carl Hanser Verlag, 2019)
The main purpose of this study is to comprehend the effects of cryomilling (CM) time on dry sliding wear behaviour of 10 wt.% TiB2 reinforced Al-12.6 wt.% Si metal matrix composites (MMCs). The MMCs were synthesised via sequential milling (mechanical alloying + cryomilling) and pressureless sintering. Indentation tests performed at a maximum load of 200 g showed that the Young's modulus and hardness of the composites increased up to 20 min of CM time. The effects of CM time and load on the composites were examined based on their tribological properties. Based on the results, the 4 h mechanical alloyed (MA'd) and 30 min CM'd sample showed the lowest wear rate under the normal load of 1 N, with its wear mechanism being predominantly oxidative. However, for the normal load of 4 N, the lowest wear rate was found in the 4 h MA'd composite, in which the dominant wear mechanism was abrasion.
Keywords: Al-Si matrix composites; Titanium diboride; Sequential milling; Pressureless sintering; Wear behaviour